Expression of immune genes in Indian major carp, Catla catla challenged with Flavobacterium columnare. Issue 94 (November 2019) - Ravindra,; Pradhan, P.K.; Paria, Anutosh; Pande, Veena; Verma, Dev K.; Arya, P.; Rathore, G.; Sood, N.
Abstract: Columnaris disease, caused by Flavobacterium columnare, is one of the important bacterial diseases responsible for large-scale mortalities in numerous freshwater fishes globally. This disease can cause up to 100% mortality within 24 h of infection and is considered to be a cause of concern for aquaculture industry. Despite being a serious disease, scarce information is available regarding host-pathogen interaction, particularly the modulation of different immune genes in response to F. columnare infection. Therefore, in the present study, an attempt has been made to study expression of important immune regulatory genes, namely IL-1β, iNOS, INF-γ, IL-10, TGF-β, C3, MHC-I and MHC-II in gills and kidney of Catla catla following experimental infection with F. columnare . The expression analysis of immune genes revealed that transcript levels of IL-1β, iNOS, IL-10, TGF-β, C3 and MHC-I were significantly up-regulated ( p < 0.05) in both the organs of the infected catla. IFN-γ and MHC-II were up-regulated in gills of infected catla whereas, both the genes showed down-regulation in kidney. The results indicate that important immune genes of C. catla are modulated following infection with F. columnare . The knowledge thus generated will strengthen the understanding of molecular pathogenesis of F. columnare in Indian major carp C. catla. Highlights: Columnaris disease, caused by Flavobacterium columnare, is a serious disease of freshwater fishes. Expression of immune genes in Catla catla following experimental infection with Flavobacterium columnare was studied. IL-1β, iNOS, IL-10, TGF-β, C3 and MHC-I was significantly up-regulated in gills and kidney. IFN-γ and MHC-II were up-regulated in gills of infected catla whereas, both the genes showed down-regulation in kidney. Information generated will strengthen the understanding of host-pathogen interaction of columnaris disease.